Does Individual Social Capital Have Any Impact on Participation In Consumer Boycotts? Research In European Countries - Grzegorz ZASUWA; Agnieszka MAREK; Grzegorz WESOŁOWSKI; Joanna NIEWIADOMA (Communications of International Proceedings, 2021)
The present study seeks to explain how links between people affect boycotting decisions, as boycotting involves collective action problems. Particularly, our investigation focuses on the three types of individual SC, namely bridging, bonding, and linking social capital. The analysis of country representative samples derived from the European Social Survey (N = 47,086) shows that one of the main predictors of consumer participation in boycotts is the possibility of signing petitions and demonstrating publicly, both of which are included in bridging SC. The first was statistically significant for all 27 analysed countries, while the second was significant for 25 of them.
Keywords: Boycott; Corporate Social Irresponsibility; Social Capital.